Development and validation of health service management competencies. Issue 2 (9th April 2018) - Liang, Zhanming; Howard, Peter F.; Leggat, Sandra; Bartram, Timothy
Abstract : Purpose: The importance of managerial competencies in monitoring and improving the performance of organisational leaders and managers is well accepted. Different processes have been used to identify and develop competency frameworks or models for healthcare managers around the world to meet different contextual needs. The purpose of the paper is to introduce a validated process in management competency identification and development applied in Australia – a process leading to a management competency framework with associated behavioural items that can be used to measure core management competencies of health service managers. Design/methodology/approach: The management competency framework development study incorporated both qualitative and quantitative methods, implemented in four stages, including job description analysis, focus group discussions and online surveys. Findings: The study confirmed that the four-stage process could identify management competencies and the framework developed is considered reliable and valid for developing a management competency assessment tool that can measure management competence amongst managers in health organisations. In addition, supervisors of health service managers could use the framework to distinguish perceived superior and average performers among managers in health organisations. Practical implications: Developing the core competencies of health service managers is important for management performance improvement and talent management. The six core management competencies identified can be used to guide the design professional development activities for health service managers. Originality/value: The validated management competency identification and development process can be applied in other countries and different industrial contexts to identify core management competency requirements.